2014
DOI: 10.1017/bec.2014.5
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Controlled Trial of Acceptance and Commitment Therapy and Cognitive-Behaviour Therapy for Generalised Anxiety Disorder

Abstract: The study examined the relative efficacy of group acceptance and commitment therapy (ACT) for generalised anxiety disorder (GAD) compared to group cognitive-behavioural therapy (CBT). Fifty-one individuals with GAD were randomly allocated to a 6-week intervention, either ACT or CBT. Participants were assessed at pre-treatment, post-treatment, and 3-month follow-up on symptom measures, quality of life, and process measures. Data from 38 participants (19 in each group) were available at post-assessment, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 35 publications
1
26
0
6
Order By: Relevance
“…ACT also encourages individuals to clarify their personal values and engage in behaviors that are consistent with these values in order to help them regulate their emotions. Randomized controlled trials have found that in adults ACT decreases: depression (Öst, 2014), psychotic symptoms (Bach and Hayes, 2002;Bach, Hayes, and Gallop, 2012;Gaudiano and Herbert, 2006;White et al, 2011), panic disorder, generalized anxiety disorder, and social anxiety (Arch et al, 2012;Avdagic, Morrissey, and Boschen, 2014), obsessive-compulsive disorder (Twohig et al, 2010), drug and nicotine dependence (Hernández-López, Luciano, Bricker, Roales-Nieto, and Montesinos, 2009;Luoma, Kohlenberg, Hayes, and Fletcher, 2012), borderline personality disorder (Gratz and Gunderson, 2006;Morton, Snowdon, Gopold, and Guymer, 2012), chronic pain (Hann and McCracken, 2014;Veehof, Oskam, Schreurs, and Bohlmeijer, 2011;Weineland, Arvidsson, Kakoulidis, and Dahl, 2012;Wetherell et al, 2011), and improves weight control (Forman et al, 2007;Juarascio, Forman, and Herbert, 2010;Lillis, Hayes, Bunting, and Masuda, 2009). Research evidence for the application of ACT with adolescents is less extensive although four randomized controlled trials have found that it can reduce depressive symptoms, unsafe sexual behaviors, chronic pain, anxiety, and stress (Hayes, Boyd, and Sewell, 2011;Livheim et al, 2014;Metzler, Biglan, Noell, Ary, and Ochs, 2000;Wicksell, Melin, Lekander, and Olsson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…ACT also encourages individuals to clarify their personal values and engage in behaviors that are consistent with these values in order to help them regulate their emotions. Randomized controlled trials have found that in adults ACT decreases: depression (Öst, 2014), psychotic symptoms (Bach and Hayes, 2002;Bach, Hayes, and Gallop, 2012;Gaudiano and Herbert, 2006;White et al, 2011), panic disorder, generalized anxiety disorder, and social anxiety (Arch et al, 2012;Avdagic, Morrissey, and Boschen, 2014), obsessive-compulsive disorder (Twohig et al, 2010), drug and nicotine dependence (Hernández-López, Luciano, Bricker, Roales-Nieto, and Montesinos, 2009;Luoma, Kohlenberg, Hayes, and Fletcher, 2012), borderline personality disorder (Gratz and Gunderson, 2006;Morton, Snowdon, Gopold, and Guymer, 2012), chronic pain (Hann and McCracken, 2014;Veehof, Oskam, Schreurs, and Bohlmeijer, 2011;Weineland, Arvidsson, Kakoulidis, and Dahl, 2012;Wetherell et al, 2011), and improves weight control (Forman et al, 2007;Juarascio, Forman, and Herbert, 2010;Lillis, Hayes, Bunting, and Masuda, 2009). Research evidence for the application of ACT with adolescents is less extensive although four randomized controlled trials have found that it can reduce depressive symptoms, unsafe sexual behaviors, chronic pain, anxiety, and stress (Hayes, Boyd, and Sewell, 2011;Livheim et al, 2014;Metzler, Biglan, Noell, Ary, and Ochs, 2000;Wicksell, Melin, Lekander, and Olsson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Die Reduktion der Erlebensvermeidung scheint ein wichtiger Wirkmechanismus zu sein, weil damit eine erhöhte Bereitschaft, auch unangenehme Erfahrungen und Gefühle zu erleben, einhergeht [21]. In RCT-Studien konnten für ACT ähnlich hohe Effekte wie für klassische KVT gefunden werden [22,23]. Öst [24] hingegen kritisiert anhand seiner Metaanalyse die Qualität solcher Studien und sieht die Wirksamkeit bei Angststörungen als noch unzureichend nachgewiesen an.…”
Section: Acceptance and Commitment Therapy (Act)unclassified
“…ACTraining is founded on the principles of Acceptance and Commitment Therapy (ACT) [2], a cognitive-behavioral therapy shown to be efficacious for treating many clinical concerns [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The ACT model, whether applied in the clinic or the workplace, leads to measurable behavior change and focuses on improving psychological flexibility.…”
Section: Acceptance and Commitment Training (Actraining) [1]mentioning
confidence: 99%